CBS tabanlı denizel mekânsal planlama sistemi ile denizüstü rüzgâr santrallerinin değerlendirilmesi: Kuzey Ege örneği - İşiaçık Çolak, Arife Tuğsan (Lisansüstü Eğitim Enstitüsü, 2021)
İçinde bulunduğumuz yüzyıl daha önce benzerine rastlanmamış bir enerji ihtiyacını beraberinde getirmiştir. Bunun temel sebebi, hiç kuşkusuz ki sanayileşme ve endüstriyel faaliyetlerin öngörülemeyen gelişimidir. Teknolojinin hızı, süreci beslemiş, dolayısıyla kullanılan enerji kaynaklarının azalması ve tükenmesi konusu günümüzün en önemli sorunlarından biri haline gelmiştir. Gereksinim duyulan enerjinin tükenebilir değil, yenilenebilir ve sürdürülebilir olması ile enerji kaynaklarının üretilebilmesi konusu birçok disiplinin enerji konusundaki çalışmalarında önemli bir araştırma alanı olmuştur. Özellikle, temiz ve tükenmeyen enerji olan rüzgâr enerjisi pek çok çalışmanın ve uygulamanın konusudur. Rüzgâr enerjisinden yararlanma konusundaki gelişmeler ve buna bağlı olarak çalışmaların ve yatırımların dünyada ve Türkiye'de paralel olduğu görünmektedir. Türkiye'nin üç tarafının denizlerle çevrili olması, denizüstü rüzgâr santrallerinden yararlanabilme avantajını ön plana çıkartmaktadır. Türkiye denizlerinin jeopolitik önemi ve özellikle uluslararası anlamda kritik öneme sahip Ege Denizi'nin, deniz üstü rüzgâr santralleri konusundaki potansiyelinden yararlanmak için çok yönlü mekânsal analizlerin gerçekleştirilmesi önemli ve gerekli görülmektedir. Bu çalışmayla Türkiye'de, enerjide dışa bağımlılığı azaltmak ve yenilenebilir enerjiden daha fazla yararlanmak amacıyla ortalama rüzgâr potansiyeli yüksek, ancak, kısıt alanlarının da çok fazla olduğu Kuzey Ege Denizi'nde, rüzgâr enerji türbinlerinin konumlandırılacağı bölgelerin belirlenmesi amaçlanmıştır. Bu bağlamda, çalışmanın birincil hedefi: Türkiye'nin Kuzey Ege deniz sahasında, potansiyel rüzgâr türbin sahalarının yer tespitinin yapılması ve uygunluk alanlarının belirlenerek, bölge için Coğrafi Bilgi Sistemleri (CBS) tabanlı bir Denizel Mekânsal Planlama Sistemi oluşturmaktır. Bu kapsamda, alternatif bölgelerin belirlenerek sıralandığı, CBS ve çok ölçütlü karar verme tekniklerinin kullanıldığı bir karar modeli uygulanmıştır. Çalışmanın ikincil hedefi ise, Kuzey Ege Denizi açık deniz türbinleri kurulumu için ideal alanların enerji verimliliğini ortaya koymak için enerji ve ekserji analizleri gerçekleştirmektir. Kuzey Ege Denizi gibi stratejik öneme sahip, uluslararası denizcilik seyir hat yoğunluğu oldukça fazla olan, çevresel hassasiyeti yüksek bir deniz alanında; denizel mekânsal planlamanın gerekliliğine göre oluşturulmuş CBS veri tabanlı bütünleşik bir uygulama ile (ÇÖKA yöntemleri ile uygun yerleri belirleme, uygun yerlerin sıralanması ve son adımda çalışma bölgelerinin enerji ve ekserji verimlilik analizi) doğruluğu ve uygunluğu yüksek açık deniz rüzgar türbinleri potansiyel alanları bu tez çalışmasının konusudur.

The century we live in has created an unprecedented energy need. The main reason for this is the development of all kinds of industries and the point reached today. The enormous breakthrough in technology has fed the process, and the energy resources used have come face to face with the danger of extinction. The largest energy source in the world is still fossil fuels. For millions of years, living species have decomposed to form fossil fuels with the effect of pressure. These resources have been used so far, and it looks like they will be used for a while. The depletion and reduction of resources have resulted in higher prices, and the excessive use of these fuels has adversely affected and continues to harm the environment. Fossil fuels are running out, which brings along the search for new energy. However, the energy sought should be renewable rather than exhaustible. The new energy sources sought should be sustainable as well as renewable. Therefore, resources must be produced without risk. The energy that constantly uses natural resources for its production and can renew itself without depletion can only be obtained from natural resources. The energy expended in this direction would also pollute the environment at deficient levels; however, nature may easily absorb this pollution. The primary source of wind energy is the sun. While the energy sought is renewable and sustainable, the sun, the source of the continuity of life, is precisely the inexhaustible source sought. Wind turbines are installed in areas with much wind and convert the movement energy of the wind into electrical energy. Wind energy occurs according to many different variables, such as the earth's rotation and surface friction. Due to the unpredictability of these variables, renewable wind energy was not preferred until recently. The installation of wind turbines led to high costs. However, these costs have decreased incomparably over the years, and thanks to technological developments, the wind has become measurable, and today wind energy has become one of the most preferred energy types. In parallel with the developments in the world, the developments in Turkey have been in a similar direction. The spatial analysis of wind power plants is thought to solve a fundamental problem because seas surround Turkey on three sides, and its geopolitical importance, especially the Aegean Sea, has critical importance, and this thesis aims at the stated purpose. The primary purpose of this study is to determine the location of potential wind turbine sites in the North Aegean sea area of Turkey and determine their suitability areas to create a Geographical Information Systems-based marine spatial planning system for the region. A decision model has been proposed in which GIS and multi-criteria decision-making techniques are used together to determine alternative regions. The criteria with the determined vector data format were made using Geographic Information Systems software. In this study, while multi-criteria decision-making techniques were used to evaluate and compare the criteria, the Fuzzy TOPSIS method was used to compare the Gökçeada, Bozcaada and Enez study areas with each other and to determine the ideal area. The main reasons for selecting this study area are the high wind speed capacity of the North Aegean Sea, the proximity of Bozcaada and Gökçeada to the mainland, and the compliance of these regions with various criteria specified in the study. However, deploying offshore wind turbines to the sea and putting the system into operation are costly investments. The necessary step to establish wind power plants in the offshore area is to ensure the efficiency of the energy to be obtained. In the last step of the study, the exergy and energy efficiency analysis to be obtained from the system on a selected sample turbine is made. For the calculation of efficiencies, five-year meteorological parameter data of the determined stations were also used.
Evaluation of offshore wind turbine site selection with GIS-based marine spatial planning system: The North Aegean sea
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Coğrafi bilgi sistemleri; Geographical information systems; Rüzgar enerjisi; Wind energy; Rüzgar türbinleri; Wind turbines